The Comparison Between START and TAI Models in Improving SMP Students' ReadingComprehension Ability - Sihombing, Triumph; Katemba, Caroline Victorine (LPPM Universitas Advent Indonesia, 2019)
This study was aimed to see whether there was a significant difference in students' improvements in reading comprehension ability after applying START (Students and teacher Actively Reading Text) and T-A-I (Team Assisted Individualization) models. This study used a quantitative research method and comparative design. The participants of the study were 63 students that were divided into two groups. Class VIIB students were taught through the START model and VIIC students were taught through the T-A-I model. The conclusion is: There was an improvement in the reading comprehension ability of students who were taught using START, categorized as moderate and T-A-I cooperative learning models, categorized as low. Moreover, there is a difference in the students reading comprehension improvement between those who acquired START and T-A-I teaching models. Keywords: Reading comprehension ability, Narrative Text, Descriptive Text, START, T-A-I, Teaching Model.